THE EFFECT OF COMMITMENT, WORK ENVIRONMENT, AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A INTERVENING VARIABEL (CASE AT PT SAI APPAREL INDUSTRIES) - Khasbana, Arina; Saddewisasi, Wyati; Sujito, Sujito; Lestari, Rohmini Indah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The level of the company's ability to produce a product from the performance quality index is one of the performance indicators. The performance quality index shows a decrease in employee performance, where performance appraisal in a company shows the profitability and sustainability of the company's operations. This study aims to analyze the effect of commitment, work environment, and compensation on employee performance with mediation of job satisfaction at PT Sai Apparel Industries. This research uses quantitative methods with stratified random sampling techniques by giving questionnaires to the entire population of two hundred employees, and one hundred and thirty- three can be processed. This research uses the Structural Equation Model-Partial Least Square (SEM-PLS) with the SmartPLS 3.2 application. The results found that commitment has no effect on job satisfaction. However, it has a positive and significant effect on employee performance. Work environment, job satisfaction, and compensation have a positive and significant effect on job satisfaction and employee performance. In addition, job satisfaction cannot mediate the relationship between commitment and compensation, but the work environment has a positive and significant effect on job satisfaction and employee performance. job satisfaction has an impact on the work environment and employee performance.